Millienium development goals for health : rising to the challenges - Wagstaff, Adam.; Claeson, Mariam; World Bank (Washington, D.C : World Bank, 2004)
This book brings together what is known about the constraints to faster progress and offer policies to address them. It also examines how the international community and the World Bank might work better with countries to achieve the Millennium Development Goals.
Includes bibliographical references and index.
osa 16/08/2016, rpm 31/01/2019, 19/02/2019
Loans
Keywords: Health promotion; Medical policy; Medical policy - cross cultural studies; Health planning - cross cultural studies